(untitled) (مجلة العلوم الإنسانية والتطبيقية, 2017)
Academic writing remains an essential skill for English learners in Libya in EFL context. English courses offered in Libya at tertiary levels mostly focus on teaching for general purposes, few concerns writing for academic purposes, even for English majors. Therefore, This paper examines the needs and lack of EFL Libyan learners who study English for academic writing purpose . Analysis of the questionnaire and learners’ texts that have been used to collect data were presented. Results indicate that most of the participants have never taken an academic English course before and that learners found a huge difficulty in academic writing skills. Therefore, an EAWP (English for Academic Writing purpose ) course is needed for learners who study at tertiary levels in Libya in order to write academic papers appropriately.